2018
DOI: 10.1161/hypertensionaha.118.11101
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Trial of the Impact of Morning or Evening Dosing of Antihypertensive Agents on 24-Hour Ambulatory Blood Pressure

Abstract: Some data suggest that nocturnal dosing of antihypertensive agents may reduce cardiovascular outcomes more than daytime dosing. This trial was designed to evaluate whether ambulatory blood pressure monitoring levels differ by timing of drug dosing. Patients aged 18 to 80 years with reasonably controlled hypertension (≤150/≤90 mm Hg) on stable therapy of ≥1 antihypertensive agent were recruited from 2 centers in London and Thessaloniki. Patients were randomized to receive usual therapy either in the morning (6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 14 publications
2
51
0
4
Order By: Relevance
“…9,22,[51][52][53][54] In contrast, there have been a few smaller-powered studies with various study designs that reported no difference between evening and morning administration of anti-hypertensive medications. 14,55 One such study, the HARMONY trial, transplantation. One study in adults with CKD found that daytime and nighttime BP were predictive of myocardial infarction, stroke, and death.…”
Section: Discussionmentioning
confidence: 99%
“…9,22,[51][52][53][54] In contrast, there have been a few smaller-powered studies with various study designs that reported no difference between evening and morning administration of anti-hypertensive medications. 14,55 One such study, the HARMONY trial, transplantation. One study in adults with CKD found that daytime and nighttime BP were predictive of myocardial infarction, stroke, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with baseline, there was no difference in nighttime SBP with 12-week-long dosing of all BP-lowering medications either in the morning or at bedtime. After adjustment for center, carry over, and period effects, nighttime SBP did not differ between the bedtime and the morning dosing regimen (between-group difference: 21.62 mm Hg; 95% CI, 25.38 to 2.15 mm Hg) (8).…”
mentioning
confidence: 86%
“…The effect of timing of antihypertensive therapy on ambulatory BP profile was explored in the 2018 Hellenic-Anglo Research into Morning or Night Antihypertensive Drug Delivery (HARMONY) trial (8). This trial enrolled 103 patients with hypertension with clinic BP #150/90 mm Hg under stable therapy for at least 3 months from 2 centers in London and Thessaloniki.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its many drawbacks, office BP measurement is still considered the golden standard for diagnosing HTN and for determining the threshold of initiation and follow-up of anti-hypertensive medications. Many studies showed that data provided by ambulatory blood pressure (ABPM) as nighttime blood pressure and dipping status are stronger predictors of cardiovascular outcome than office BP [3]. Because of its cost and lack of availability in many health centers, ABPM cannot yet replace the office BP measurements, so it is reserved to situations where office BP alone cannot explain the clinical circumstances of the patient.…”
Section: Introductionmentioning
confidence: 99%